The Application of Moringa Leaf Extract Moringa oleifera (Lam, 1785) to Increase Non Specific Immunity of Tilapia Oreochromis niloticus (Linnaeus 1758) Infected by Aeromonas hydrophila - Nurlia Subryana; Wardiyanto Wardiyanto; Oktora Susanti (Department of Aquaculture, 2020)
Non-specific immunities are the main defenses in the fish seed. One of the natural ingredients as a source of immunostimulants is Moringa oleifera. Moringa leaves contain flavonoids, alkaloids, terpenoids and saponins as immunostimulant agents. Immunostimulants are biological that can enhance the immune system. The purpose of this study was to determine the effect of Moringa leaf extract in increasing non-specific immunity in tilapia (Oreochromis niloticus) seeds infected by Aeromonas hydrophila. In giving Moringa leaf extract intramuscular injection of 0.1 mL/fish with concentrations of 50 mg, 75 mg, and 100 mg. In this research method, a completely randomized design (CRD) was used with 4 treatments and 3 replications, each aquarium containing 12 tilapia measuring 8-10 cm each. Feeding on tilapia is done every 3 times a day namely morning, afternoon, and evening. The parameters tested were leukocytes, differential leukocytes, erythrocytes, phagocytic activity, and index. The results showed that the administration of Moringa leaf’s extract injected into tilapia seed can increase non-specific immunity, which are total leukocytes, total erythrocytes, differential leukocytes, activity, and phagocytosis index.